Digital Transformation Trends in Vocational Education in Indonesia During the COVID-19 Pandemic - Muktiarni,; Dwiyanti, Vina; Sari, Ana Ramdani (Journal of Technical Education and Training, 2021)
The COVID-19 Pandemics has forced the changes of many aspects of life, including vocational education. Schools must adapt to the new condition and have no other option but to shift the conventional learning activities to online learning. However, online learning becomes especially more challenging for vocational schools that focus on practical lessons. The limited access to the internet and technological tools in many remote and rural areas also become problems in delivering the learning activities. Therefore, teachers and schools need to offer various learning modes and digital platforms to ensure that the students can still access the lesson flexibly. The study aims to discover the trend in the use of digital transformation of online learning during the COVID-19 pandemic. It is also to find out the best means of delivering the students' education for the future. The study uses a quantitative approach and uses a simple survey to collect the data. The study involved 110 teachers in various vocational schools in Bandung, while the questionnaire was collected using google forms. The data then presented in graphs then analyzed and compared to a literature review from related studies. The study shows that in synchronous learning, Google Meet is the most popular option for video-conferencing (82%). In comparison, video-assisted learning is the most popular (94,45%) in asynchronous learning among vocational teachers. In terms of using the Learning Management System, all teachers use Google Classroom to manage the classes. It is also interesting that most teachers prefer to use more than one digital platform to deliver their lessons. In conclusion, vocational teachers gravitate more towards free, easy-to-use, engaging platforms and require little effort and preparation to operate. They also need flexibility and variations to use digital platforms to adjust the lesson to their capabilities, and the student needs accordingly.